SICKLE CELL ANEMIA IN QUILOMBOLAS: A LITERATURE REVIEW - Borges, Renan Pires Ferreira; Canutto, Rafael Felipe Carvalho; Gomes, Kassita Alvarenga; Rodrigues Junior, Carlos Alberto; Dias, Fellipe Camargo Ferreira; Guedes, Virgílio Ribeiro (Revista de Patologia do Tocantins, 2018)
Introduction: Sickle cell disease is a generic term that encompasses a set of hematological disorders linked to structural changes in blood cells, leading to the production of an abnormal hemoglobin called HbS, the 'S' being derived from English sickle. The objective of this study was to discuss the profile of sickle cell anemia in quilombola communities by reviewing the existing literature in order to provide updated data to professionals dealing with this population. Development: The prevalence of HbS heterozygotes in Brazil is higher in the North and Northeast regions, between 6% and 10%, and considerably lower in the South and Southeast regions, with prevalence between 2% and 3%. In this study, it was found that 6.6% to 11.5% of the population of quilombolas in the state of Tocantins had abnormal hemoglobins. Conclusion: Few studies evaluate the prevalence of hemoglobinopathies in quilombola communities. Since quilombolas usually live in isolated communities of society, the chances of marriages between individuals with sickle cell trait are greater than in the general population, thus increasing the probability of being born to individuals affected by the disease. Keywords: Sickle cell disease, Quilombolas, Epidemiology. RESUMO Introdução: Doença falciforme é um termo genérico que engloba um conjunto de desordens hematológicas ligadas a alterações estruturais das células sanguíneas, levando à produção de uma hemoglobina anormal denominada HbS, sendo o ‘S’ derivado do inglês sickle. O objetivo deste estudo foi abordar o perfil da anemia falciforme nas comunidades quilombolas por meio de revisão da literatura existente, a fim de fornecer dados atualizados aos profissionais que lidam com essa população. Desenvolvimento: No Brasil, a prevalência de heterozigotos HbS é maior nas regiões do Norte e Nordeste, entre 6% e 10%, e consideravelmente menor nas regiões Sul e Sudeste, com uma prevalência entre 2% e 3%. Neste estudo, encontrou-se que 6,6% a 11,5% da população de quilombolas no estado do Tocantins apresentaram hemoglobinas anormais. Conclusão: Poucos estudos avaliam a prevalência de hemoglobinopatias em comunidades quilombolas. Visto que os quilombolas costumam viver em comunidades isoladas da sociedade, as chances de ocorrerem casamentos entre indivíduos com traço falciforme, tornam-se maiores que na população em geral, aumentando assim a probabilidade de nascerem indivíduos acometidos pela doença. Palavras-chave: Doença falciforme, Quilombolas, Epidemiologia.